The Experience of Pregnancy in Women Living With HIV: A Meta‐Synthesis of Qualitative Evidence. (July 2017) - Leyva‐Moral, Juan M.; Piscoya‐Angeles, Patricia N.; Edwards, Joan E.; Palmieri, Patrick A.
Abstract : N/A: The lived experience of pregnancy from the perspectives of women living with HIV (WLWH) is not well understood. We aimed to understand the meaning of pregnancy for WLWH. A meta‐synthesis was conducted to review and integrate qualitative studies about the phenomena; 12 databases were used to perform the search in English, Spanish, and Portuguese. Articles using qualitative methods published in peer‐reviewed journals were included. Data were analyzed using the meta‐synthesis method. We found that, for pregnant WLWH, pregnancy evolved as a mediated experience of commitment and dedication. The vital life experience of pregnancy was defined as an interplay of emotions, coping strategies, and feelings of satisfaction. Pregnancy in WLWH was experienced and impacted by societal beliefs, as the women focused all their efforts to take care of themselves and their babies.